The Effect of the Think Pair Share (TPS) Cooperative Learning Model and Learning Motivation on Students' Learning Outcomes in Citizenship Education - Michael Fredrik Sihombing; Sanggam Magda Lasmaria Siahaan; Sabar Dumayanti Sihombing (STAI MA'ARIF MAGETAN, INDONESIA, 2026)
This study aims to examine the effect of the Think Pair Share (TPS) cooperative learning model and learning motivation on student learning outcomes in Civic Education subject among eleventh-grade students at SMA Negeri 5 Pematangsiantar. This study employed a quantitative approach with data collected through a Likert-scale questionnaire. A total of 69 students were selected as the sample using purposive random sampling technique. Data were analyzed using multiple linear regression, F-test, t-test, and correlation and determination coefficients with the assistance of IBM SPSS 26. The results indicate that the TPS learning model has a positive and significant effect on learning outcomes with a t-value of 8.185 (sig. 0.000), learning motivation has a positive and significant effect with a t-value of 6.216 (sig. 0.000), and simultaneously both variables have a significant effect with an F-value of 68.627 (sig. 0.000) and a coefficient of determination of 67.5%. These findings confirm that the implementation of the TPS model combined with high learning motivation contributes substantially to improving student learning outcomes.